Geriatric assessment in daily oncology practice for nurses and allied health care professionals: Opinion paper of the Nursing and Allied Health Interest Group of the International Society of Geriatric Oncology (SIOG). Issue 5 (September 2016) - Burhenn, Peggy S.; McCarthy, Alexandra L.; Begue, Aaron; Nightingale, Ginah; Cheng, Karis; Kenis, Cindy
Abstract: The management of older persons with cancer has become a major public health concern in developed countries because of the aging of the population and the steady increase in cancer incidence with advancing age. Nurses and allied health care professionals are challenged to address the needs of this growing population. The International Society of Geriatric Oncology (SIOG) Nursing and Allied Health (NAH) Interest Group described key issues that nurses and allied health care professionals face when caring for older persons with cancer. The domains of the Geriatric Assessment (GA) are used as a guiding framework. The following geriatric domains are described: demographic data and social support, functional status, cognition, mental health, nutritional status, fatigue, comorbidities, polypharmacy, and other geriatric syndromes (e.g. falls, delirium). In addition to these geriatric domains, quality of life (QoL) is described based on the overall importance in this particular population. Advice for integration of assessment of these geriatric domains into daily oncology practice is made. Research has mainly focused on the role of treating physicians but the involvement of nurses and allied health care professionals is crucial in the care of older persons with cancer through the GA process. The ability of nurses and allied health care professionals to perform this assessment requires specialized training and education beyond standard oncology knowledge.